ERICA: prevalence of metabolic syndrome in Brazilian adolescents - Maria Cristina C Kuschnir; Katia Vergetti Bloch; Moyses Szklo; Carlos Henrique Klein; Laura Augusta Barufaldi; Gabriela de Azevedo Abreu; Beatriz Schaan; Gloria Valeria da Veiga; Thiago Luiz Nogueira da Silva; Maurício T L de Vasconcellos; Ana Júlia Pantoja de Moraes; Ana Mayra Andrade de Oliveira; et al. (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To determine the prevalence of metabolic syndrome and its components in Brazilian adolescents. METHODS We evaluated 37,504 adolescents who were participants in the Study of Cardiovascular Risks in Adolescents (ERICA), a cross-sectional, school-based, national study. The adolescents, aged from 12 to 17 years, lived in cities with populations greater than 100,000 inhabitants. The sample was stratified and clustered into schools and classes. The criteria set out by the International Diabetes Federation were used to define metabolic syndrome. Prevalences of metabolic syndrome were estimated according to sex, age group, school type and nutritional status. RESULTS Of the 37,504 adolescents who were evaluated: 50.2% were female; 54.3% were aged from 15 to 17 years, and 73.3% were from public schools. The prevalence of metabolic syndrome was 2.6% (95%CI 2.3-2.9), slightly higher in males and in those aged from 15 to 17 years in most macro-regions. The prevalence was the highest in residents from the South macro-region, in the younger female adolescents and in the older male adolescents. The prevalence was higher in public schools (2.8% [95%CI 2.4-3.2]), when compared with private schools (1.9% [95%CI 1.4-2.4]) and higher in obese adolescents when compared with nonobese ones. The most common combinations of components, referring to 3/4 of combinations, were: enlarged waist circumference (WC), low HDL-cholesterol (HDL-c) and high blood pressure; followed by enlarged WC, low HDL-c and high triglycerides; and enlarged WC, low HDL-c, high triglycerides and blood pressure. Low HDL was the second most frequent component, but the highest prevalence of metabolic syndrome (26.8%) was observed in the presence of high triglycerides. CONCLUSIONS ERICA is the first Brazilian nation-wide study to present the prevalence of metabolic syndrome and describe the role of its components. Despite the prevalence of Metabolic Syndrome being low, the high prevalences of some components and participation of others in the syndrome composition shows the importance of early diagnosis of this changes, even if not grouped within the metabolic syndrome.